Digital Literacy: Students’ Perception toward Advanced Grammar Interactive E-Books in the English Department of Universitas Negeri Padang - Fitrawati, Fitrawati; Syarif, Hermawati; Zaim, M; D. Perrodin, David; Zakiyah, Muflihatuz (International Journal of Language Pedagogy, 2022)
The use of multimedia as a part of digital literacy also becomes the demand of this 21st-century education. The material has to be more technological and supports student-oriented learning methods. The use of this kind of technology also can be applied in English lessons like grammar. In the English Department of Universitas Negeri Padang, multimedia has been used in grammar classes, specifically in advanced grammar classes for students in the academic year 2018, called interactive e-books. This study analyzed students’ perceptions of using this interactive e-book in advanced grammar classes. The design of this study was descriptive research. The population of this study was the students in the English Department in the academic year 2018. Then the sampling used purposive sampling where the sample was the class with 32 students used interactive e-books for their advanced grammar course. The instrument for this study was the questionnaire, divided into three sections: interface, interactivity, and material. The data were collected by descriptive statistical calculation. The result of this study was that students had a positive perception of using interactive e-books in advanced grammar classes. Hence, the students’ perceptions can be used to improve better interactive e-books used in the teaching and learning process in grammar class.